Kárate superior 7. Katas Jitte, Hangetsu y Empi - Juan María García Díez (Universidad de León, 2012)
Masatoshi Nakayama. Madrid: Ediciones Tutor, 2007. <span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-bidi-font-weight: bold;" lang="PT-BR">143 páginas. 23,50x18,5 cm. I.S.B.N.: 978-84-7902-628-8.